Pediatric emergence delirium: Canadian Pediatric Anesthesiologists' experience. Issue 2 (12th November 2015) - Rosen, H. David; Mervitz, Deborah; Cravero, Joseph P.
Summary: Introduction: Pediatric emergence agitation/delirium (ED) is a cluster of behaviors seen in the early postanesthetic period with negative emotional consequences for families and increased utilization of healthcare resources. Many studies have looked at identifying risk factors for ED and at pharmacologic regimens to prevent ED. There are few published reports on treatment options and efficacy for established ED episodes, and essentially no data concerning current practice in the treatment of ED. We sought to elicit the experience and opinions of Canadian Pediatric Anesthesiologists on the incidence of ED in their practice, definitions and diagnostic criteria, preventative strategies, treatments, and their perceived efficacy. Methods: A web‐based survey was sent to pediatric anesthesiologists working at academic health science centers across Canada. The participants were selected based on being members of the Canadian Pediatric Anesthesia Society (CPAS), which represents the subspecialty in Canada. All members of CPAS who had e‐mail contact information available in the membership database were invited to participate. A total of 209 members out of the total of 211 fulfilled these criteria and were included in the study population. Results: The response rate was 51% (106/209). Of respondents, 42% felt that ED was a significant problem at their institutions, with 45% giving medication before or during anesthesia to prevent the development of ED. Propofol was the most common medication given to prevent ED (68%) and to treat ED (42%). Total intravenous anesthesia (TIVA) was considered by 38% of respondents as a technique used to prevent ED. Medications used for treatment included propofol (42%), midazolam (31%), fentanyl (10%), morphine (7%), and dexmedetomidine (5%), with 87% of respondents rating effectiveness of treatment as 'usually works quickly with one dose'. Discussion: We present information on current practice patterns with respect to prophylaxis and treatment of ED among a specialized group of pediatric anesthesiologists and highlight the importance of further research in improving the treatment of this common and challenging peri‐anesthetic occurrence. Abstract :